Desenvolvimento de módulo inversor monofásico: aplicação em sistema fotovoltaico - Ble, Dedeha Ange Lauraine (2023)
This work aims to develop a prototype of a single-phase half-bridge voltage inverter module for application in photovoltaic systems. The module consists of a non-isolated direct current to direct current (DC-DC) boost converter designed to raise the voltage from the 30 V solar panel up to 120 V. Additionally, it includes a static direct current to alternating current (DC-AC) converter to generate alternating voltage for powering AC loads of up to 60 V with a half-bridge configuration at 60 Hz. Electrical characterization has been conducted to validate the suitable operation of the system. The results of experimental measurements indicate that the proposed system can be supply AC loads, since the 30 V DC (typical value of open circuit voltage of a solar panel) has been elevated up to 120 V. This work promotes the use of clean and sustainable electrical source supplies.